2011
DOI: 10.1248/bpb.34.1291
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Kaempferol against a 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Induced Mouse Model of Parkinson's Disease

Abstract: Parkinson's disease (PD) is a progressive, age-related, neurodegenerative disorder characterized by bradykinesia, rigidity, resting tremor and gait disturbance 1) ; it occurs in 1-2% of the population over the age of 60 years.2) Typical neuropathologic features of the disease are dopaminergic neuron degeneration in the substantia nigra and the presence of eosinophilic intracytoplasmic inclusions (Lewy bodies) in the residual dopaminergic neurons. The most widely used mouse model of PD is produced by systemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…In 6-OHDA-treated rats, quercetin enhanced spatial memory (Sriraksa et al, 2012) while myricetin suppressed iron toxicity . In MPP + /MPTP models, quercetin and myricetin were effective in vitro (Mercer et al, 2005;Zhang et al, 2011a) and kaempferol was reported to be effective in vivo (Li and Pu, 2011). In the rotenone models, however, only kaempferol showed positive effect against rotenone toxicity in SH-SY5Y cells.…”
Section: Flavonoidsmentioning
confidence: 98%
“…In 6-OHDA-treated rats, quercetin enhanced spatial memory (Sriraksa et al, 2012) while myricetin suppressed iron toxicity . In MPP + /MPTP models, quercetin and myricetin were effective in vitro (Mercer et al, 2005;Zhang et al, 2011a) and kaempferol was reported to be effective in vivo (Li and Pu, 2011). In the rotenone models, however, only kaempferol showed positive effect against rotenone toxicity in SH-SY5Y cells.…”
Section: Flavonoidsmentioning
confidence: 98%
“…223 Kaempferol has a neuroprotective effect against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced neurotoxicity in a mouse PD model. 224 However, bioavailability is limited to approximately 2% after oral administration. 225 Nanosized kaempferol enhances the antioxidant activity of kaempferol.…”
Section: Nanokaempferolmentioning
confidence: 99%
“…KM has been highlighted over the past years due to its multifunctional efficacies in various diseases such as Parkinson's disease and cancer. [33][34][35] It has been deemed as a drug for the management of inflammatory processes of airway diseases due to its potent anti-inflammatory and antioxidant characteristics. [33][34][35] In addition, other studies have also been demonstrated that KM can block not only lipopolysaccharideinduced NF-κB signaling but also suppress stress-induced MUC expression.…”
Section: )mentioning
confidence: 99%
“…[33][34][35] It has been deemed as a drug for the management of inflammatory processes of airway diseases due to its potent anti-inflammatory and antioxidant characteristics. [33][34][35] In addition, other studies have also been demonstrated that KM can block not only lipopolysaccharideinduced NF-κB signaling but also suppress stress-induced MUC expression. 31,36,37) However, the beneficial effects of KM on PQ-mediated ROS stress in BEAS-2B cells have not been well elucidated yet.…”
Section: )mentioning
confidence: 99%